British Travellers, Nova Scotia’s Black Communities and the Problem of Freedom to 1860 - McNairn, Jeffrey (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractBritish travellers commented frequently on those of African descent they encountered in colonial Nova Scotia, especially their material conditions and prospects. Those who published accounts at the peak of the campaign to abolish slavery in the British Empire intervened directly in debates about whether former slaves would prosper under conditions of colonial freedom. They cast themselves as objective imperial observers and Nova Scotia’s black communities as experiments in free labour. Attending to how most crafted and reworked their observations to argue against emancipation in the West Indies situates Nova Scotia and travel texts in intellectual histories of the production of colonial knowledge, debates about slavery, and the nature of nineteenth-century liberalism.